2018
DOI: 10.1093/infdis/jiy429
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Soluble Mediators of the Host Response in Ebola Virus Disease

Abstract: BackgroundThe pathophysiology of Ebola virus disease (EVD) is still poorly understood. This study aimed at identifying soluble biomarkers that inform on disease mechanisms.MethodsFifty-four soluble mediators of the immune, coagulation, and endothelial system were measured in baseline and follow-up samples from hospitalized patients with EVD, using Luminex technology. Cross-sectional expression levels and changes over time were correlated with outcome.ResultsLevels of circulating proinflammatory cytokines and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 30 publications
6
27
0
1
Order By: Relevance
“…In fatalities, overexpression of numerous cytokines and chemokines was observed, regardless of their functions. This unbalanced immune response is associated with a poor prognosis and has been described for various epidemics and defined as a cytokine storm (7,8,16,25,30,31). In our study, chemokine expression was the most highly dysregulated, as chemokines were released in very large amounts in fatalities.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 54%
See 1 more Smart Citation
“…In fatalities, overexpression of numerous cytokines and chemokines was observed, regardless of their functions. This unbalanced immune response is associated with a poor prognosis and has been described for various epidemics and defined as a cytokine storm (7,8,16,25,30,31). In our study, chemokine expression was the most highly dysregulated, as chemokines were released in very large amounts in fatalities.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 54%
“…In survivors, the expression of all of the molecules tested was transitory, with some synthesized at high levels for only a few days. Another study did not report any peak of cytokine expression in survivors when the date after admission was used as time line, suggesting that patients came at the peak of the illness (25). Interestingly, IL-38 and sCD40L levels were elevated in survivors from day 7, the day that viremia dropped.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Intriguingly, the protective role of type I IFN responses is controversial, since the apparent antiviral function during the earliest stages of infection may, in turn, fuel pathogenesis during the later stages of viral disease. That seems to be the case not only for HIV-1 [43], but also for EBOV [76], where clinical data collected during human outbreaks have indicated that elevated levels of circulating IFNα, as well as upregulation of type I IFN-inducible genes, correlates with fatal disease outcome [64,[77][78][79]. Thus, HIV-1 and EBOV infections trigger an immune activation state that upregulates Siglec-1 expression on DCs, a situation that might favor early viral dissemination events in an otherwise antiviral environment [80].…”
Section: Viral Sensing and Immune Activation Triggers Siglec-1 Inductmentioning
confidence: 99%
“…1 Ebola virus causes a strong inflammatory response, destroys the host's immune response, and causes multiple organ disorder syndrome. 6 Ebola remains a priority disease for the World Health Organization (WHO) owing to the risk of relapse it poses, and the lack of effective vaccines and antiviral drugs to combat it. 8 In May 2015, the first case of Middle East respiratory syndrome (MERS) was reported in Guangdong, China.…”
Section: Emerging Infectious Diseasesmentioning
confidence: 99%